Global sourcing of digital services : micro and macro perspectives : 11th Global Sourcing Workshop 2017, La Thuile, Italy, February 22-25, 2017, Revised selected papers /: micro and macro perspectives : 11th Global Sourcing Workshop 2017, La Thuile, Italy, February 22-25, 2017, Revised selected papers. (2017) - Unknown
No abstract available